Dari Desentralisasi Jaringan ke [De]sentralisasi Kuasa: Dinamika, Kekuatan dan Pukulan Balik - Rendy Pahrun Wadipalapa (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2013)
Power works in a network where each actor in it is always in a position of power to run and run. Power can not be owned, but circulated, disseminated each other, and exchanged in a wide distribution network. Each of these actors want to remain in the circulation of inter-and intra network so as to follow the current is to survive. Decentralization efforts the network has changed the balance of political power. However, forms of social network communication technology today, although it has tremendous value to be used as power and political consolidation, also risk a backlash. Decentralized system that exists today, in some ways has a crack and centralized, in some aspects still looks centralized: they are too vulnerable to state retaliation and control.